The Kaiser’s lost African empire and the Alternative für Deutschland: Colonial guilt-denial and authoritarian populism in Germany (Historia, 2021)
This article examines the role which the “imaginary” of the empire that Germany lost in 1919 plays in the contemporary German extreme right, and especially its leading expression, the Alternative für Deutschland (AfD). It focuses on the symbolic importance of the former colonies in South West Africa / Namibia and East Africa / Tanzania and of the less emotionally charged, although also significant, German ‘informal empire’ connections to South Africa. The article highlights that the AfD draws on a considerable legacy of political activism concerning Africa stretching back through the colonial revanchist nationalism of the Weimar era, the global network of the Nazi Party’s “Foreign Organisation”, and the post-war populism of Franz Josef Strauß. AfD ideologues glorify the achievements of the Kaiserreich, and emphasise that Germany has nothing to be ashamed of, in relation to its record in the colonial era. With the recent demands from Namibia for the payment of German reparations for the 1904-7 genocide in that country, this past has become a very live issue in German politics, and the AfD has made much of its opposition to any admission of German culpability. The article also shows how the AfD portrays itself as the defender of the German minority in Namibia and of white South Africans, whose position is represented as a warning of what happens when white people allow racial “others” to attain political power. The analysis seeks to avoid simple “culturalist” /historicist explanations of the presence of these issues in contemporary politics, embedding its account in the continuities of significant social, economic and strategic relationships between southern Africa and Germany.  Hierdie artikel ondersoek die rol wat die “imaginêre” van die ryk, wat Duitsland in 1919 verloor het, speel in die hedendaagse Duitse vêrregse beweging, en veral wat betref sy vernaamste manifestasie, die AfD. Dit fokus op die simboliese belang van die voormalige kolonies in Suidwes-Afrika/Namibië en Oos-Afrika/Tanzanië en die minder belaaide, maar steeds belangrike, Duitse “informele ryk” se bande met SuidAfrika. Die artikel belig die feit dat die AfD hom beroep op ’n noemenswaardige nalatenskap van politieke aktivisme wat betref Afrika, wat so vêr terugstrek as die koloniale revanchistiese nasionalisme van die Weimar-era, die globale netwerk van die Nazi Party se “Oorsese Organisasie”, en die na-oorlogse populisme van Franz Josef Strauß. AfD ideoloë verheerlik die prestasies van die Kaiserreich, en beklemtoon dat Duitsland niks het om oor skaam te wees wat betref sy koloniale verlede nie. Met Namibië se onlangse eis om die betaling van Duitse reparasies vir die 1904-7 volksmoord in daardie land, het die verlede ’n baie lewendige vraagstuk in die Duitse politiek geword, en die AfD het veel gewag gemaak van sy teenstand wat betref enige erkenning van Duitse aandadigheid. Die artikel wys ook hoe die AfD homself uitbeeld as die beskermheer van die Duitse minderheid in Namibië en van wit Suid-Afrikaners, wie se posisie uitgebeeld word as ’n waarskuwing oor wat gebeur wanneer wit mense die “rasse-ander” toelaat om politieke mag te verkry. Die analise poog om vereenvoudigde “kulturistiese”/historistiese verklarings oor die teenwoordigheid van hierdie vraagstukke in hedendaagse politiek te vermy deur sy weergawe te grond op die kontinuïteit van belangrike sosiale, ekonomiese en strategiese verhoudings tussen Suider-Afrika en Duitsland.
Keywords: Alternative für Deutschland; German colonialism; Herero reparations; Germans in Namibia; Franz Josef Strauß; Duitse kolonialisme; Herero reparasies; Duitsers in Namibië